Estrés laboral y malestar psicológico en los empleados del Cuerpo de Bomberos del cantón Balsas, periodo 2021-2022 - Diaz Romero, Jamileth Anahí (2022)
The World Health Organization defines work stress as emotional, psychological, cognitive and behavioral reactions to demands that exceed the worker's knowledge and skills. OMS (2020). In the present investigation it has been proposed: to determine the influence of work stress in the psychological discomfort of the employees of the Fire Department of Balsas canton; measure the level of job stress and job stressors in the aforementioned population, through the application of the OIT-OMS Job Stress Questionnaire; to evaluate the degree of psychological discomfort in the aforementioned population through the application of the SCL-90-R Symptom Inventory of L. Derogatis; and finally suggest a psychological prevention plan that allows the reduction of work stress levels and psychological discomfort. The methodology used is quantitative, exploratory, field, explanatory and correlational. Techniques such as questionnaires, direct observation and detailed instruments were applied in the previously exposed objectives. Finally, there is no statistically significant correlation between work stress and psychological distress